Trauma-Focused Cognitive Behavioral Therapy Applied to Childhood Traumatic Grief in the Aftermath of a Motor-Vehicle Accident: A School-Based Case Study. (October 2014) - Stevens, Anne E.; Michael, Kurt D.
Symptoms of posttraumatic stress, depression, and unresolved grief can appear in children and adolescents following the witnessing or experiencing of a traumatic event and respond with intense fear, helplessness, or horror. Those who lose a loved one in a traumatic manner can develop childhood traumatic grief (CTG), where typical grieving is hindered by trauma symptoms, causing significant impairment in daily functioning, relationships, and academic pursuits. The following is a case study describing a trauma-focused cognitive behavioral approach to treat posttraumatic stress disorder and CTG in a 16-year-old driver of a motor vehicle accident in which his peer was killed. A graduate student clinician provided treatment under supervision within the context of a school mental health program. The results of the intervention were associated with significant reductions in symptoms and impairments in daily living. The implications of these data and recommendations for clinicians treating CTG are provided.